Ask the Audience: Determining Organizational Identity of a State Extension Agency - Jennifer Ray; Lauri M. Baker; Quisto Settle (Journal of Applied Communications, 2015)
This study explored organizational identity of one state extension agency to determine strategies for building future messaging in external branding materials. Thirty-nine focus groups were conducted to assess how internal audiences (employees and board members) perceive, feel, and think about the organization. Two of the 15 major themes found were 1) Extension is a link between the university and the people and 2) Extension provides research-based, credible information. Participants identified strongly with the vision statement and official slogan communicated by leaders prior to the study. The organization should build upon this identity when solidifying a brand image. Previous research indicates Extension should also proceed with caution regarding the themes of providing valuable services and information for low or no cost and not selling anything.
Keywords: Extension; organizational identity; branding; values; culture; Association for Communication Excellence Conference